1996
DOI: 10.1002/art.1780390613
|View full text |Cite
|
Sign up to set email alerts
|

In situ hybridization analysis of synovial and systemic cytokine messenger RNA expression in superantigen‐mediated Staphylococcus aureus arthritis

Abstract: Objective. To investigate patterns of synovial and systemic cytokine messenger RNA (mRNA) expression in mice with superantigen-mediated Staphylococcus aureus arthritis.Methods. Mice were inoculated intravenously with 1 X lo7 colony-forming units of toxic shock syndrome toxin-1-producing S aureus LS-1. Synovial tissues and spleens were obtained at varying time intervals after bacterial inoculation, and examined for mRNA expression of interleukin-lp (IL-lp), IL-4, IL-10, IL-12, tumor necrosis factor a (TNFa), TN… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
28
0

Year Published

1997
1997
2011
2011

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 49 publications
(29 citation statements)
references
References 47 publications
1
28
0
Order By: Relevance
“…Moreover, the upregulation of proinflammatory mediators in response to HKBA or L-Omp19 was accompanied by the appearance of a mixed inflammatory infiltrate in the synovium. The local upregulation of proinflammatory cytokines and MMPs agrees with previous findings in mouse models of septic arthritis by staphylococci, streptococci, and Borrelia burgdorferi (7,50,58) and also agrees with our own findings for a human case of brucellar septic bursitis (52).…”
Section: Downloaded Fromsupporting
confidence: 92%
See 2 more Smart Citations
“…Moreover, the upregulation of proinflammatory mediators in response to HKBA or L-Omp19 was accompanied by the appearance of a mixed inflammatory infiltrate in the synovium. The local upregulation of proinflammatory cytokines and MMPs agrees with previous findings in mouse models of septic arthritis by staphylococci, streptococci, and Borrelia burgdorferi (7,50,58) and also agrees with our own findings for a human case of brucellar septic bursitis (52).…”
Section: Downloaded Fromsupporting
confidence: 92%
“…The preponderant role of TNF-␣ as an MMP inducer in FLS agrees with the findings of several previous studies (12,32,33,53). It has been shown that TNF-␣ is upregulated in the joints of mice with S. aureus arthritis and that the local secretion of TNF-␣ in the joint cavity gives rise to an increased severity of arthritis (58). The second potential contribution of phagocytes to joint damage is through their secretion of MMPs upon activation by microbial molecules during phagocytosis or in response to stimulation with proinflammatory factors.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…IFN-g is a Th1 cytokine of importance in the pathogenesis of septic arthritis [7]. The serum levels of this cytokine were, however, essentially unaltered in the L-NMMA-treated group compared with controls (882 Ϯ 146 mU/ml versus 609 Ϯ 314 mU/ ml) in infected animals.…”
Section: Serological and Haematological Manifestationsmentioning
confidence: 96%
“…Macrophages play an important role in the process of joint destruction. For example, macrophage-derived cytokines such as IL-1b and tumour necrosis factor-alpha (TNF-a), found during S. aureus infection in the joint tissue [7], contribute to bone and cartilage degradation [8]. In contrast, polymorphonuclear cells are important in the defence mechanism during S. aureus infection ( [9] and Verdrengh, unpublished results).…”
Section: Introductionmentioning
confidence: 99%